THE NOTION OF VERTICAL AGREEMENT AND VERTICAL RESTRAINT IN VERTICAL BLOCK EXEMPTION REGULATION 2022/720 - Fišer-Šobot, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
In the year of 2022 the European Commission adopted Regulation 2022/720 on the application of Article 101(3) of the Treaty on the Functioning of the European Union to categories of vertical agreements and concerted practices as well as the accompanying Guidelines on vertical restraints. The adoption of the Regulation was necessary, primarily because of the changes in the market, which are reflected in the growth of e-commerce, intensive use of information technologies in the sale and distribution of goods and in providing services, the emergence of new types of vertical agreements, as well as the affirmation of certain business models. Regulation 2022/720 governs the block exemption of vertical agreements and applies to vertical agreements that contain vertical restraints. In this paper are analyzed vertical agreement and vertical restraint as key concepts of the Regulation 2022/720.